Twelfth International Conference on Machine Vision (ICMV 2019) 2020
DOI: 10.1117/12.2559447
|View full text |Cite
|
Sign up to set email alerts
|

Next integrated result modelling for stopping the text field recognition process in a video using a result model with per-character alternatives

Abstract: In the field of document analysis and recognition using mobile devices for capturing, and the field of object recognition in a video stream, an important problem is determining the time when the capturing process should be stopped. Efficient stopping influences not only the total time spent for performing recognition and data entry, but the expected accuracy of the result as well. This paper is directed on extending the stopping method based on next integrated recognition result modelling, in order for it to b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…For the validity of the stopping methods as it is described in [34] any metric function ρ between the text string recognition results can be used, provided that it satisfies the triangle inequality. For experiments in [34] and [35] a normalized version of the Generalized Levenshtein Distance (GLD) [37] was used. For calculating GLD a metric ρ C must be defined on the set of individual character classification results (on individual rows of the matrices).…”
Section: Existing Methods Descriptionmentioning
confidence: 99%
See 4 more Smart Citations
“…For the validity of the stopping methods as it is described in [34] any metric function ρ between the text string recognition results can be used, provided that it satisfies the triangle inequality. For experiments in [34] and [35] a normalized version of the Generalized Levenshtein Distance (GLD) [37] was used. For calculating GLD a metric ρ C must be defined on the set of individual character classification results (on individual rows of the matrices).…”
Section: Existing Methods Descriptionmentioning
confidence: 99%
“…The described stopping method was tested on text string recognition results without membership estimations [34], using ROVER [38] as a combination algorithm. Later it was tested with another per-frame recognition method and with an extended text string recognition result model [35] using a combination algorithm [30] based on a ROVER approach. In both experiments, it was shown that using such an approach for a given average number of processed frames the lower error level could be achieved and vice versa.…”
Section: Existing Methods Descriptionmentioning
confidence: 99%
See 3 more Smart Citations